How Return on Investment and Residual Income Performance Measures and Risk Preferences Affect Risk-Taking - Brown, Jason L.; Martin, Patrick R.; Sprinkle, Geoffrey B.; Way, Dan (Management Science, 2023)
Return on investment (ROI) and residual income (RI) are two important accounting measures that are commonly used to evaluate managers’ performance, and evidence suggests that both ROI and RI can help motivate long-term investments. Research is limited, though, regarding whether ROI and RI differentially affect managers’ actions, and, more specifically, research has not examined the effects of ROI and RI on risk-taking. We conduct an experiment to examine the separate and interactive effects of individuals’ risk preferences and ROI and RI performance measures on risk-taking in capital investment decisions. We predict and find that the use of ROI as a performance measure leads to riskier choices, as compared with RI, and that this effect is concentrated in relatively more risk-averse individuals. We also provide process evidence that reveals some of the ways in which ROI and RI performance measures affect decision making. Collectively, our results contribute to literature examining the effects of accounting information and performance measures on managers’ risk-taking behaviors. This paper was accepted by Suraj Srinivasan, accounting. Funding: Financial support from the Kelley School of Business at Indiana University is gratefully acknowledged. Supplemental Material: Data files are available at https://doi.org/mnsc.2022.4398 .